2005
DOI: 10.1016/j.euje.2004.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac echocardiography: an ideal guiding tool for device closure of interatrial communications

Abstract: Background This study sought to evaluate safety and radiation exposure when using intracardiac echocardiography (ICE) in comparison to transesophageal echocardiography (TEE) in order to guide transcatheter closure of interatrial communications. Methods Eighty patients (44 males, 36 females, mean age 46, SD 13 years) undergoing device closure of atrial septal defect (n Z 12) or patent foramen ovale (n Z 68) had the procedure guided by ICE (n Z 50, group 1) or TEE (n Z 30, group 2). In group 1, all procedural st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…Furthermore, ICE can provide a better view of the inferior septum which TEE cannot provide. 8,9) There are two studies comparing ICE and TEE in the literature, and both reported excellent agreement. 6,10) For the reasons mentioned above, we do not believe further randomized trials between TEE and ICE are urgently needed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, ICE can provide a better view of the inferior septum which TEE cannot provide. 8,9) There are two studies comparing ICE and TEE in the literature, and both reported excellent agreement. 6,10) For the reasons mentioned above, we do not believe further randomized trials between TEE and ICE are urgently needed.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, there is a higher probability that TEE will interfere with the fluoroscopy due to its larger profile and position of the esophagus. 9,15,19,20) Certainly, ICE has some drawbacks. First, it needs another vascular access which is at least 9F and via a femoral vein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-cardiac echocardiography provides a unique high quality image of the right heart cavities [9][10][11][12] and is a high resolution tool both for detecting venous air embolism and intra-cardiac air. Our previous study showed that intra-cardiac echocardiography is the most sensitive method for intra-cardiac air detection, allowing the visualisation of individual air bubbles with air detected within the right ventricle immediately after its intra atrial appearance [13].…”
mentioning
confidence: 99%